Building Ethical Awareness on the Internet Through Student Rewards and Punishment - Ai Santi; Sulasman Sulasman; Asep Saepul Rochman (Comprehensive: Jurnal Ilmu Pendidikan dan Keguruan, 2025)
This study addresses the critical gap between theoretical understanding and practical application of digital ethics among students at Islamic junior high school MTs Al-Khaeriyah. The rapid digital transformation has created an urgent need for effective digital ethics education, particularly in Islamic educational institutions. Using a qualitative case study approach, this research examines the implementation of reward and punishment systems integrated with Islamic values to enhance students' digital ethics awareness. Data were collected through participatory observation, in-depth interviews with 15 students and 5 Islamic education teachers, and documentation analysis over three months. The findings demonstrate that non-material rewards including public recognition, digital certificates, and point systems, combined with restorative punishments such as reflective writing assignments and digital content creation tasks, significantly improved students' ethical awareness and behavior in digital spaces. The study concludes that a systematic approach combining behavioral theory with Islamic educational principles effectively bridges the theory-practice gap in digital ethics education. These results highlight the importance of consistent implementation, teacher collaboration, and parental involvement in developing comprehensive digital ethics education programs within madrasah environments, contributing to the creation of responsible digital citizens who embody Islamic values in their online interactions.